THAUMATOMYRMEX STRIPS MILLIPEDES FOR PREY - A NOVEL PREDATORY BEHAVIOR IN ANTS, AND THE 1ST CASE OF SYMPATRY IN THE GENUS (HYMENOPTERA, FORMICIDAE) - Brandao, CRF; Diniz, JLM; Tomotake, E. M. (Birkhauser Verlag Ag, 1991)
We describe, for the first time, the predatory behaviour of Thaumatomyrmex ants on millipedes of the family Polyxenidae, based on field observations of T. atrox and a field and laboratory study of T. contumax. The capture of the prey and the removal process of its body-covering setae by the ants before they eat the millipede are described. This specialized behaviour in at least two species of the genus, belonging to two distinct groups of species, indicates a general trend in Thaumatomyrmex. We coupled this study with a comparative morphological analysis of the mouthparts and digestive tube of these and other Thaumatomyrmex species. Also, we report the first case of sympatry in the genus, which suggests that Thaumatomyrmex includes several species. and not only one highly variable taxon, as hypothesized earlier.
Keywords: THAUMATOMYRMEX; TAXONOMY; COMPARATIVE MORPHOLOGY; PREDATION; POLYXENIDAE